Hubungan Hipotermi Dengan Waktu Pulih Sadar Pasca General Anestesi di Ruang Recovery Room - Suyanti Suyanti; Cemy Nur Fitria; Amriana Amriana (Jurnal Sains dan Kesehatan, 2021)
Background: Pre-operation is the initial stage to prepare the patient as much as possible, more than two-thirds of patients waiting for surgery experience anxiety because it is their first time undergoing spinal anesthesia surgery. As a result of the patient's intense preoperative anxiety, there is a possibility that the operation cannot be carried out. The way to overcome anxiety is through deep breathing relaxation techniques. Objective: To determine the effect of deep breathing relaxation on anxiety in preoperative patients. Research methods: This research uses quantitative research design using Quasy Experiment, namely an experimental design carried out without randomization. This research was conducted at PKU Muhammadiyah Gombong Hospital in the operating room in February 2024. This population consisted of 42 patients in one month with a research sample of 30 respondents. This research instrument uses the APAIS questionnaire. This research technique uses purposive sampling. Results: The data that can be generated when using the deep breathing relaxation technique is 30 respondents using the pre test-post test technique. During the pre-test, those experiencing moderate anxiety amounted to 40.0%, severe anxiety amounted to 40.0%, the most severe anxiety/panic amounted to 20.0%. At the time of the post test, those experiencing mild anxiety were 66.7%, and those experiencing moderate anxiety were 33.3%. Conclusion: When the observation was carried out, there was a decrease in the level of anxiety, so that the respondent's anxiety had reduced.